Characterization of a Raman Spectroscopic and Holographic System for Gas‐Liquid Flows in Microchannels. Issue 8 (27th April 2017) - Schurr, Daniela; Guhathakurta, Jajnabalkya; Simon, Sven; Rinke, Günter; Dittmeyer, Roland
Abstract: The description and prediction of the highly transient processes on the molecular scale in gas‐liquid Taylor flows in microchannels are a great challenge. Due to a lack of in situ measurement techniques with satisfactory spatial and temporal resolution, existing models and numerical simulations of reactive two‐phase flows are poorly developed. The Raman spectroscopic and holographic system presented herein overcomes shortcomings regarding the high temporal resolution and concomitant difficulties with the high energy densities that must be coupled into microstructured devices to give good limits of detection. It gives insight into the concentration profiles in the liquid phase within the microchannel to study the interaction between hydrodynamics, mass transport, and reaction kinetics. Abstract : An in situ analysis system offers high temporal and spatial resolution for dealing with transient two‐phase flows in microchannels. Raman spectroscopy and holography are synchronized and spatially calibrated to determine the position of a bubble with respect to the spot at which the Raman spectra are acquired. Despite short integration times, a good limit of detection is achieved.